Evaluasi Produksi Alat Gali Muat dan Alat Angkut sebagai Upaya Pencapaian Target Produksi Clay Area 242 PT. Semen Padang - Ihsanul Rifki; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2018)
Abstract. Clay mining PT. Semen Padang from area 242 with target to 2000 ton/day uses a combination of 2 units of Kobelco SK 200 excavators and 16 units of HINO FM 260 Ti dump truck. The number of dump trucks active in a month an average of 10 units/day. Daily production target area of 242 is 2000 ton/day, while the range of daily production data ranges from 364.61 Ton - 1037.1 Ton. The low daily production that underlies the authors do this research. Efforts that can be made to efficiently achieve production targets of 2000 ton / day in 242 areas are a review of the equipment production capacity so that bulk when loading material from 14 to 16, swing angle improvement from 180o to 90o to reduce cycle time excavator, active dump truck 10/17 minimum to 15/17 units, effective time excavator repair from 34% to 74%, effective dump truck time from 50% to 75%.Keywords:  Clay, Excavator, Dump truck, Production, Match Factor